The power of collaboration and realism in social transition planning: an improved foundation for success in remote Australia - Wilson-Clark, C; Macmillan, G; Winn, R; Martinez, C (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Social transition planning has traditionally been led by the operator as the party responsible for closing the asset and minimising negative impacts for communities and other stakeholders. In this paper, WSP and Rio Tinto’s cross-disciplinary social and economic specialists argue for the benefits of social transition planning as a joint responsibility of a multi-stakeholder group, comprising key organisations and governments, who maintain a community presence post-closure, in close partnership with the closing operation. We suggest high order priority should be given to First Nations peoples as landowners, social and economic leaders, and custodians of culture and country. To support this approach, input on detailed data-driven studies (in the tradition of robust socio-economic impact assessments) that predicts and discloses the reality of the post-closure scenario should be obtained and analysed with the multi-stakeholder group governing the study. The paper draws on recent experience delivering such a study at the Rio Tinto-operated Gove bauxite mine in the Australian Northern Territory, on the Gove Peninsula in East Arnhem Land. Here, Traditional Owners and their organisations contribute to and drive outcomes through their membership and active contribution to the Gove Peninsula Futures Reference Group (GPFRG). The group has articulated a clear post-mining vision for Nhulunbuy and the Gove Peninsula. Group members have worked with the study team to interrogate data, share and test potential investment options, and adapt approaches and planning scenarios to progress towards improved outcomes. This highly collaborative model requires sophisticated engagement skills and a degree of compromise or ‘letting go’ on the part of the operator, which can challenge typical approaches. We suggest the model can be implemented in a way which supports operators who are genuinely interested in leaving communities with positive legacies focused on a successful and sustainable alternative future. The authors would like to express their acknowledgement of and deep respect for the Traditional Owners and Custodians of the land, sea and waters of the Gove Peninsula in East Arnhem Land, the Yolŋu. It is with the Yolŋu vision for a vibrant and self-determined future that this paper is delivered.
Keywords: social transition